Molecular Cloning and Chaperone Activity of DnaK from Cold-adapted Bacteria, KOPRI22215 - Sung, Min-Sun; Im, Ha-Na; Lee, Kyung-Hee (Bulletin of the Korean Chemical Society, 2011)
Psychrophilic bacteria have acquired cold-resistance in order to protect themselves against freezing temperatures, which would otherwise be lethal. DnaK/DnaJ/GrpE systems are molecular chaperones which facilitate proper folding of newly synthesized proteins. Efficient folding processes are of great importance especially in a cold environment, such as the Arctic. In order to understand the protection mechanisms of psychrophilic bacteria against cold temperatures, we have explored a genome of KOPRI22215, tentatively identified as Psychromonas arctica, whose genome sequence has not yet been discovered. With an aim of searching for a coding gene of DnaK from KOPRI22215, we have applied a series of polymerase chain reactions (PCR) with homologous primers designed from other Psychromonas species and LA PCR in vitro cloning. 1917 bp complete coding sequence of dnaK from KOPRI22215 was identified including upstream promoter sites. Recombinant plasmids to overexpress PaDnaK along with EcDnaK (DnaK of E. coli) were then constructed in pAED4 vector and the pET-based system to induce PaDnaK expression by IPTG. Characterization assays of expressed PaDnaK were carried out by measuring survival rates upon 4 day incubation at 4 ^oC: a refolding assay as molecular chaperone, and ATPase assay for functional activity. Taking account of all the data together, we conclude that PaDnaK was identified, successfully expressed, and found to be more efficient in providing cold-resistance for bacterial cells. KCI Citation Count: 2